2010
DOI: 10.1007/s11113-010-9189-7
|View full text |Cite
|
Sign up to set email alerts
|

How do Recent Population Trends Matter to Climate Change?

Abstract: Population, Climate change, Demographic trend, Mitigation and adaptation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(63 citation statements)
references
References 57 publications
2
56
0
5
Order By: Relevance
“…The released GHGs and heat have induced a strong influence on temperature spatial distribution in recent years (Li and Zhao, 2012), especially in developing countries, where the economic policy relies on extensive growth, which favours results, despite lower resource efficiency and energy waste. Jiang and Hardee (2011) noted that main factors influencing anthropogenic effects on aerosol emission are economic growth, technological change, and population growth, which cannot be easily simulated using numerical models (Zhou et al, 2010). Recently, better understanding about the effects of human activities on dryland expansion in various scenarios has been achieved (Huang et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…The released GHGs and heat have induced a strong influence on temperature spatial distribution in recent years (Li and Zhao, 2012), especially in developing countries, where the economic policy relies on extensive growth, which favours results, despite lower resource efficiency and energy waste. Jiang and Hardee (2011) noted that main factors influencing anthropogenic effects on aerosol emission are economic growth, technological change, and population growth, which cannot be easily simulated using numerical models (Zhou et al, 2010). Recently, better understanding about the effects of human activities on dryland expansion in various scenarios has been achieved (Huang et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…The regional environment change has a close relationship with local population density and economic development level. Jiang and Hardee (2011) found that economic growth, technological changes, and population growth are the main elements of anthropogenic effects on emissions, which cannot be simulated easily by numerical models (Zhou et al, 2010). More recently, there have been some studies on understanding the implications of population growth, worker structure, and economic intensity for various scenarios of environmental change.…”
Section: Introductionmentioning
confidence: 99%
“…into the resulting increase with the increase of energy consumption with aging degree. This conclusion and scholars Zhu Qin [9], Chen Jing [10] similar results, the influence of the aging of China's Carbon emissions may not be significant or it is not clear. The aging of many research results also show that the effects of energy use and Carbon emissions mechanism is very complex, and it will lead to increase or decrease of energy consumption and Carbon emissions is not clear.…”
Section: ) Po Coefficient Was Not Significant Statistically It Showmentioning
confidence: 61%